2015
DOI: 10.1177/0145482x1510900406
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Attitudes and uses of Music by Adults with Visual Impairments and those who are Sighted

Abstract: Introduction This study investigated attitudes (intrapersonal, interpersonal, and communal) toward, and uses of, music among people with visual impairments compared with those who are sighted to investigate the potential of music as a means of communication and social expression. Method A total of 137 participants (63 visually impaired, 74 sighted) were recruited from six cities in South Korea. Participants, aged 20 to 39 years, were asked to complete a 30-question survey on music attitudes and use, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
1
14
0
2
Order By: Relevance
“…This finding is consistent with previous studies reporting that musicing, with an aim to improve social relationships, could help individuals with AVI to form positive relationships with others, thereby reducing their sense of isolation and promoting mutual exchange ( Metell, 2015 ). The findings also agreed with a previous study on the function of music for social groups, which reported that music, to individuals with AVI, could make a marked contribution to promoting the exchange among group members and enabling them to acquire a sense of belonging ( Park et al, 2015 ). Thus, music groups should be utilized actively to help individuals with AVI overcome psychosocial problems such as feelings of loss, alienation, and isolation.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous studies reporting that musicing, with an aim to improve social relationships, could help individuals with AVI to form positive relationships with others, thereby reducing their sense of isolation and promoting mutual exchange ( Metell, 2015 ). The findings also agreed with a previous study on the function of music for social groups, which reported that music, to individuals with AVI, could make a marked contribution to promoting the exchange among group members and enabling them to acquire a sense of belonging ( Park et al, 2015 ). Thus, music groups should be utilized actively to help individuals with AVI overcome psychosocial problems such as feelings of loss, alienation, and isolation.…”
Section: Discussionsupporting
confidence: 92%
“…Visually impaired people have the same needs as normally sighted people with respect to becoming functional members of society (Tuttle & Tuttle, 2004). Some visually impaired people actively use other senses (especially hearing) to compensate for their lack of vision and can enjoy music to the same extent as the normally sighted (Park, Chong, & Kim, 2015). As an auditory medium, music can play a vital role in the lives of visually impaired people because of its availability and practicality in terms of personal use (Rostohar, 2006).…”
mentioning
confidence: 99%
“…Visually impaired people can also use music as a tool for social communication as well as a source of personal enjoyment (Robb, 2003; Wolffe, Koenig, Sacks, & Lewis, 2003; Wolffe & Sacks, 1997). Some of them enjoy participating in group music activities, such as choirs, vocal bands, wind ensembles, and karaoke singing (Park, Chong, & Kim, 2015). Music can facilitate social connections, build mastery and competence, and provide solace in adversity (Werner & Smith, 2001).…”
mentioning
confidence: 99%